Way forward - Abdul Rahim, Asiah; Aripin, Srazali; Suhaimi, Hanis Najeha; Fatimah, Siti; Ismail, Megat Mohammad Aqif (KAED Universal Design Unit (KUDU), 2022)
This chapter concludes the research, analysis, data, and discovery on Masjid Jamek Sultan Abdul Samad. This whole writing consists of seven (7) chapters altogether, elaborately explaining the outcomes of the study that has been done for subject AAR 3302 of the 20th Heritage Studies, 2020.